Study of the phase transition in polycrystalline (Ba₀.₉₀Pb₀.₁₀)(Ti₀.₉₀Sn₀.₁₀)O₃ - Kajtoch, C.; Bąk, W.; Garbarz-Glos, B. (Condensed Matter Physics, 2013)
Polycrystalline sample of (Ba₀.₉₀Pb₀.₁₀)(Ti₀.₉₀Sn₀.₁₀)O₃ was obtained by means of a conventional ceramic technology. The dielectric measurements were performed depending on temperature and frequency of electric measuring field. The character of the phase transitions of (Ba₀.₉₀Pb₀.₁₀)(Ti₀.₉₀Sn₀.₁₀)O₃ ceramics strongly depends on the presence of Pb in the sample. The obtained results pointed out the diffused character of phase transition. The temperature dependence of the dielectric properties showed that the phase transition from the paraelectric phase to ferroelectric one takes place at the same temperature (Tm=367 K). It does not depend on the frequency of the measuring electric field. A change of the value of the parameter γ takes place in the paraelectric phase.